Dimensi Kemanusiaan Seorang Imam: Tinjauan Etika Kebajikan Kristiani - Lina, Paskalis; Kota, Dominggus Mite (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2024)
The reality of scandals involving priests in the Catholic Church has recently caused deep wounds to the Church. This fact also requires the Church to pay serious attention to the human formation of her priests. This study aims to retrace the human qualities of a priest that can contribute to the development of virtues necessary in his vocation and priestly ministry. By utilizing an analytical study of texts and various official Church documents, the authors seek to bring to the fore the main qualities that the Church requires and expects from a priest. As a result, firstly, the author finds that there is a correlation between the personal qualities of a priest and the development of the virtues required in the vocation and ministry of the priesthood. Secondly, the study also found that it is important for these human qualities to be shaped during the process of formation throughout life, so that they become virtues that are deeply rooted in a priest and his ministry.